Fenomena Islamophobia Di Inggris: Analisis Pengaruh Mohamed Salah Dan Implikasinya - Zainal Mustofa, Ahmad (STAI Publisistik Thawalib Jakarta, 2022)
This article describes the impact and influence generated by Mo Salah in reducing the paradigm of islamophobia in the city of Merseyside, England. In this discussion, the author uses Mead's theory of Symbolic Interactionism. The method used in this research is descriptive analytical research method. This study concludes that the phenomenon of islamophobia in Europe and the United States gives negative sentiments to non-Muslims, and the UK is no exception. In this paper, the author provides an overview of condition in Merseyside before and after arrival of Mo Salah. The interaction made by Mo Salah with the surrounding environment has a big influence on supporters of the Merseyside city team, Liverpool. The friendly and humble figure, as well as the attractive game displayed by Mo Salah, changed the paradigm of islamophobia into admiration for Islam. Mo Salah's presence as a Muslim footballer is able to have a positive impact. The level from fear of Islam was reduced and he changed the image of Islam in the world by interaction of symbolism with the football media. He is a humble person and always respects both his fellow players and his fans.